Dissemination of definitions and concepts of allergic and hypersensitivity conditions. Issue 1 (December 2016) - Tanno, Luciana; Calderon, Moises; Smith, Helen; Sanchez-Borges, Mario; Sheikh, Aziz; Demoly, Pascal
Abstract Background Allergy and hypersensitivity can affect people of any age and manifest with problems in a range of organ systems. Moreover, they can have a significant impact on the quality of life of patients and their families. Although once rare, there is presently an epidemic of allergic disorders with associated considerable societal consequences. Our understanding of the pathophysiology of these disorders has changed substantially over the last 20 years. In the light of these developments, the Joint Allergy Academies have made concerted efforts to ensure that these are reflected in the current definitions and concepts used in clinical allergy and to ensure these are reflected in the forthcoming International Classification of Diseases-11 (ICD-11). Objective In this review, we seek to provide an update on the current definitions and concepts in relation to allergic disorders. Results Once the new section has been built in the ICD-11 to address allergic and hypersensitivity conditions, we have been moving actions to try to support awareness by disseminating updated concepts in the field. Aligned with the ICD and the WAO philosophy of being global, this document presents fundamental and broad allergy concepts to strengthen the understanding by different health professionals worldwide, besides to support the formation of in training students. Conclusion This current review intends to be accepted and used universally by all health professionals involved in diseases' classification and coding and, therefore, contribute to improve care and outcomes in this increasing sub-section of the world's population.